IKKINChI TARTIBLI AYLANMA SIRTLARDA GEODEZIK ChIZIQLAR - Bayturayev, A.M.; Kalbaeva, Y.M. (SCIENCE and SOCIETY, 2025)
The article determines the general form of the equation of geodesics by solving the differential equation of geodesics lying on a second-order surface and studies the location of these geodesics on the surface.
Keywords: surface; point; vector; geodesic curve; tangent plane; cone; cylinder; right helicoid; metric tensor; Christoffel symbols